Pediatric cardiologyPercutaneous atrial septal defect closure by using jugular venous access in a case with interrupted inferior vena cava - Narin, Nazmi; Pamukcu, Ozge; Baykan, Ali; Argun, Mustafa; Ozyurt, Abdullah; Uzum, Kazim (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2014)
Femoral venous approach is the classical route of percutaneous atrial septal defect (ASD) closure. But in certain circumstances alternative routes are used. In this report percutaneous ASD closure in a case with interrupted vena cava by jugular venous approach is discussed. Percutaneous closure through femoral venous route was planned in a 6-year-old girl with ASD. Because of interrupted vena cava the jugular venous route was used. Having knowledge of this anatomical variation is important for interventionalists before performing femoral venous approach. Percutaneous transjugular venous access is a feasible alternative route in paediatric population for ASD closure.